Organogels as lipid profile improvers in meat and dairy matrices - García-Andrade, Mayela (Universidad Autónoma de Tamaulipas, 2019)
The structuring of edible oils, through organogelation, has a promising potential in food applications, when used as substitutes for saturated fat in some meat and dairy products of high consumption demand, in order to improve their lipid profile. Organogels are viable for this substitution, which is related to the nutritional improvement demanded by the current consumer, due to the negative effect of saturated fats on health. The objective of this review was to analyze different formulations of organogels, applied in meat-dairy matrices and their impact on the final properties of such food products, implemented as a substitute for saturated fat. The findings indicate that the replacement of saturated fat, by this type of materials, mainly affects the physicochemical properties, modifies the original flavor of the food and improves its lipid profile; However, they still do not meet the expectations of the final consumer due to the unique qualities of solid fat, which represents the main barrier to overcome for its application in an industrial scale production and sale to the market. It is necessary to develop new formulations, similar to those qualities, to achieve  consumer  acceptance.